Impact of Particulate Matter 2.5 in Acne Vulgaris: A Literature Review - Afren I; Kurniawati Y; Diba S; Aryani IA; Argentina F (RSUP Dr Moh Hoesin Palembang, 2024)
Air pollution is the contamination of any chemical, physical or biological agent that alters the characteristics of the atmosphere. The main environmental pollutants consist of nitrogen dioxide (NO2), sulfur dioxide (SO2), carbon monoxide (CO), heavy metals, particulate matter (PM)10 and PM2.5. Particulate matter is a heterogeneous mixture of small particles and liquids consisting of organic chemicals, acids, metals, soil or dust particles. Hair has a diameter of 50-70 µm, while PM10 is 2.5-10 µm and PM2.5 is < 2.5 µm. Air pollution can induce or aggravate skin diseases including acne vulgaris. Particulate matter2.5 triggers skin inflammation and stimulates inflammatory acne lesions through lipid peroxidation and Aryl hydrocarbon receptor (AhR) signaling. Interleukin (IL)-1α and IL-8 are elevated in inflammatory lesions of acne compared to normal skin, showing their role in the exacerbation of acne. The main preventive and therapeutic strategies against air pollution-induced skin damage consist of preventing the penetration of air pollutants through the skin and hair follicles, removing pollutants, improving skin barrier function, increasing skin hydration, and reducing inflammation, as well as preventing collagen and elastin degradation.